Enhancing students' entrepreneurial mindset: a Swedish experience. Issue 7 (14th August 2017) - Lindberg, Erik; Bohman, Håkan; Hulten, Peter; Wilson, Timothy
Abstract : Purpose: The purpose of this paper is to report on the test of a pedagogical intervention to enhance students' entrepreneurial mindset on a university course. Design/methodology/approach: The course where the authors tested the new course design is a mandatory one in the business school's undergraduate business program. Pre- and post-evaluations of the students' opportunity recognition (OR) and individual entrepreneurial orientation (IEO) were carried out to measure the effects of an intervention aimed at enhancing these capabilities. Findings: The results from paired-samples t -tests indicate significant positive changes (enhancements) of the students' OR and IEO. The positive effects of the intervention methods are accounted for as evidence of the benefits of applying pedagogical methods that fit the learning style of young adults. Practical implications: The findings suggest that students' mindsets can be positively affected by an intervention tailored to enhance their OR and IEO capabilities. The findings have implications for curriculum development because the strengthening of these capabilities is a precondition for further development of the participants' innovative and creative thinking, as well as their entrepreneurial orientation. Since innovative and entrepreneurial activities have a positive impact on economies worldwide, the authors encourage the adaption of the intervention methods applied in this study in other settings. Originality/value: This paper reports the results of a pedagogical intervention aimed at enhancing students' entrepreneurial mindset. The findings from the study demonstrate that the applied intervention method supports the development of functional skills, which complement the conceptual knowledge gained from other courses in the undergraduate program.